Understanding the effect of circadian cycle in zebrafish development and behavior. - Nagaswetha, Sodi (IISER Mohali, 2024)
Biological rhythm refers to the internal regulation of various life activities of an organism, which are determined by the specific time structure sequences of everyone. The zebrafish (Danio rerio) is a popular model organism for research for a variety of reasons, including ease of care, rapid external development of optically transparent embryos, more embryo production, fully genome sequenced and genetic similarity to humans. Our study is aimed at understanding the effects of the circadian cycle on zebrafish. We observed that effects of circadian cycle on the zebrafish. It significantly impacts reproduction, embryo production, development, growth, survival, locomotion and pigmentation. We have demonstrated the importance of the circadian clock on cell proliferation following injury. Red light led to reduced reproductive ability and poor survival (100% mortality). In summary, these findings revealed that lighting conditions are crucial factors influencing zebrafish development and growth.
Keywords: Biological; organism; pigmentation